2016
DOI: 10.1002/14651858.cd011364.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided arterial cannulation for paediatrics

Abstract: We identified moderate-quality evidence suggesting that ultrasound guidance for radial artery cannulation improves first and second attempt success rates and decreases the rate of complications as compared with palpation or Doppler auditory assistance. The improved success rate at the first attempt may be more pronounced in infants and small children, in whom arterial line cannulation is more challenging than in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 30 publications
1
44
1
2
Order By: Relevance
“…However, it is sometimes difficult, especially in small children with urgent circumstances. Recently, a systematic review including 444 arterial cannulations in a pediatric population showed that ultrasound guidance improves the first‐ and second‐attempt success rates of radial artery cannulation in children . However, it included 5 studies with elective surgical settings, where patients were sedated, and the study operators were anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is sometimes difficult, especially in small children with urgent circumstances. Recently, a systematic review including 444 arterial cannulations in a pediatric population showed that ultrasound guidance improves the first‐ and second‐attempt success rates of radial artery cannulation in children . However, it included 5 studies with elective surgical settings, where patients were sedated, and the study operators were anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review including 444 arterial cannulations in a pediatric population showed that ultrasound guidance improves the first-and second-attempt success rates of radial artery cannulation in children. 26 However, it included 5 studies with elective surgical settings, where patients were sedated, and the study operators were anesthesiologists. Under similar conditions, ultrasound guidance was favored over palpation, 16,23 and Doppler auditory assistance 27 was favored in infants and small children.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,46,47,69,73 Despite the numerous applications, great potential for patient care, and recent growth in the use of POCUS in anesthesia, there are still barriers that prevent it from being a current standard practice and challenges in establishing anesthesia-specific guidelines. Ultrasound-assisted physical examination [4][5][6] Regional anesthesia 7,8 Transthoracic echocardiography [9][10][11][12][13][14] Vascular access [15][16][17][18][19] Transesophageal echocardiography [20][21][22][23] Arterial access [24][25][26] Lung ultrasound 5,[27][28][29][30][31] Airway management [32][33][34][35][36] Volume assessment 3,5,10,37-39 Thoracentesis 15,[40][41][42][43][44] Abdominal ultrasound 37,…”
Section: Résumémentioning
confidence: 99%
“…As cited by the authors, a Cochrane review concluded that ultrasound increased the rate of successful percutaneous arterial cannulation. 10 However, a recent meta-analysis reports that although ultrasound was effective and safe, heterogeneity among studies makes it difficult to interpret data and draw definitive conclusions. 11 In this era of evidence-based medicine, the goal is to impose standards after careful analysis of outcome data, yet some of the most basic practices are based on anecdotal evidence.…”
mentioning
confidence: 99%